Statistics Topics Training For High School Teachers in Padang - Admi Salma; Dodi Vionanda; Dony Permana; Fadhillah Fitri; Dina Fitria; Zilrahmi Zilrahmi (Fakultas MIPA Universitas Negeri Padang, 2022)
One of a part mathematics subjects for high school students is statistics. Some statistics topics were usually studied by university students, but now they are studied by high school students. Teachers have difficulty teaching the topic to students for several reasons. The training is needed in order to improve the ability and knowledge of teachers about the statistics topics . The training was given to high school mathematics teachers in Padang under group named MGMP. There are 25 participans of the training. The results of activity evaluation showed an increase in the knowledge of statistics topics. In conclusion, this activity has been effectively carried out and can help the mathematics teachers to deeply understanding statistical topics